Aaron Copland and his world - Oja, Carol J., 1953-; Tick, Judith (Princeton, N.J. ; Woodstock : Princeton University Press, 2005)
Aaron Copland and His World reassesses the legacy of one of America's best-loved composers at a pivotal moment--as his life and work shift from the realm of personal memory to that of history. This collection of seventeen essays by distinguished scholars of American music explores the stages of cultural change on which Copland's long life (1900 to 1990) unfolded: from the modernist experiments of the 1920s, through the progressive populism of the Great Depression and the urgencies of World War II, to postwar political backlash and the rise of serialism in the 1950s and the cultural turbulence of the 1960s. Continually responding to an ever-changing political and cultural panorama, Copland kept a firm focus on both his private muse and the public he served. No self-absorbed recluse, he was very much a public figure who devoted his career to building support systems to help composers function productively in America. This book critiques Copland's work in these shifting contexts. The topics include Copland's role in shaping an American school of modern dance; his relationship with Leonard Bernstein; his homosexuality, especially as influenced by the writings of André Gide; and explorations of cultural nationalism. Copland's rich correspondence with the composer and critic Arthur Berger, who helped set the parameters of Copland's reception, is published here in its entirety, edited by Wayne Shirley. The contributors include Emily Abrams, Paul Anderson, Elliott Antokoletz, Leon Botstein, Martin Brody, Elizabeth Crist, Morris Dickstein, Lynn Garafola, Melissa de Graaf, Neil Lerner, Gail Levin, Beth Levy, Vivian Perlis, Howard Pollack, and Larry Starr.
Between memory and history : an introduction / Carol J. Oja and Judith Tick -- Part I. Scanning a life. Copland and the prophetic voice / Howard Pollack ; Founding sons : Copland, Sessions, and Berger on genealogy and hybridity / Martin Brody -- Part II. Copland's greater cultural world. "To become as human as possible" : the influence of André Gide on Aaron Copland / Paul Anderson ; Copland and American populism in the 1930s / Morris Dickstein ; From the New York avante-garde to Mexican modernists : Aaron Copland and the visual arts / Gail Levin ; Making an American dance : "Billy the Kid", "Rodeo", and "Appalachian Spring" / Lynn Garafola -- Part III. Copland's inner circle. Dear Aaron, dear Lenny : a friendship in letters / Vivian Perlis ; Aaron Copland and Arthur Berger in correspondence / edited and introduced by Wayne D. Shirley -- Part IV. Analytic perspectives. War drums, tolling bells, and Copland's piano sonata / Larry Starr ; Copland's gift to be simple within the cumulative mosaic complexities of his ballets / Elliott Antokoletz -- Part V. Political edges. Copland and the politics of Americanism / Elizabeth B. Crist ; From orient to occident : Aaron Copland and the sagas of the prairie / Beth E. Levy ; Aaron Copland, Norman Rockwell, and the "Four Freedoms" : the office of war information's vision and sound in "The Cummington Story" (1945) / Neil Lerner ; "Aaron Copland Meets the Soviet Composers" : a television special / transcribed and edited by Emily Abrams -- Part VI. Copland and his public. Aaron Copland and the Composers' Forum-Laboratory : a post-concert discussion, February 24, 1937 / transcribed and edited by Melissa de Graaf ; Copland on television : an annotated list of interviews and documentaries / compiled by Emily Abrams -- Part VII. Reconfiguring Copland's world. Copland reconfigured / Leon Botstein.
Includes bibliographical references and index.
JSTOR
Keywords: Copland, Aaron, -- 1900-1990.; Copland, Aaron, -- 1900-1990.; Copland, Aaron, -- 1900-1990; Composers -- United States -- Biography; Compositeurs -- États-Unis -- Biographies; BIOGRAPHY & AUTOBIOGRAPHY -- Composers & Musicians; MUSIC -- Genres & Styles -- Classical; MUSIC -- Reference; Composers; United States; Biographies